Perencanaan Dinding Penahan Tanah pada Ruas Jalan Negeri Wakasihu Kabupaten Maluku Tengah: Retaining Walls Planning on Wakasihu State Road Section, Central Maluku Regency - Wusurwut, Sahril Iyan; Betaubun, Renny James; Latar, Sjafrudin (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
JL.Province located in Negeri Wakasihu, Central Maluku Regency is one of the provincial roads affected by landslides due to its location near a fairly high slope/cliff in Negeri Wakasihu, Central Maluku.The landslide disaster occurred due to the influence of bad weather in the form of high intensity rain accompanied by strong winds that hit Negeri Wakasihu, so a solution was needed in the form of planning to build a retaining wall. The method used in the research is by using the theory and empirical formulas according to Rankine regarding active earth pressure and passive earth pressure on retaining walls and the Terzaghi method regarding soil bearing capacity. The planned retaining wall is a gravity type retaining wall with a height (H) = 4 M, bottom width (B) = 2.8 m, top width (T) = 0.6 m, and (Df) = 0.57 m. The safety factor obtained from the calculation results is that the retaining wall is stable against shear forces with a value of 4.67 > 1.5 (Safe) and the wall is stable against overturning forces with a value of 3.35 (SAFE).